Investigational agents for epithelial ovarian cancer. Issue 5 (October 2005) - Muggia, Franco; Kosloff, Rebecca
Ovarian cancer is the leading cause of gynecologic cancer deaths and accounts for 4% of women's cancer diagnoses and 5% of all cancer mortalities. Despite the ability of current chemotherapy and cytoreductive surgery to put patients in remission, most patients with advanced cancer will eventually relapse. Many advances in the treatment of ovarian cancer have been reported in the past several years and a historical background is provided. Attention will then turn to analogs of current chemotherapeutic agents, new cytotoxic drugs, targeted molecular therapy, intraperitoneal therapy and immunotherapy. This review will give a perspective on current drugs, potential agents and upcoming clinical trials.